2011
DOI: 10.1093/sysbio/syr071
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Bayesian Coalescent Method of Species Delimitation

Abstract: A Bayesian coalescent-based method has recently been proposed to delimit species using multilocus genetic sequence data. Posterior probabilities of different species delimitation models are calculated using reversible-jump Markov chain Monte Carlo algorithms. The method accounts for species phylogenies and coalescent events in both extant and extinct species and accommodates lineage sorting and uncertainties in the gene trees. Although the method is theoretically appealing, its utility in practical data analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
232
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(245 citation statements)
references
References 49 publications
10
232
0
3
Order By: Relevance
“…genetic, morphological, ecological, biogeographic) are used to delimit species [25,[50][51][52]. In the case of Mecistops, we present results from three molecular and two morphological species diagnostic approaches that unambiguously support two highly divergent taxa.…”
Section: Discussion (A) Multiple-criteria Species Delimitationmentioning
confidence: 95%
“…genetic, morphological, ecological, biogeographic) are used to delimit species [25,[50][51][52]. In the case of Mecistops, we present results from three molecular and two morphological species diagnostic approaches that unambiguously support two highly divergent taxa.…”
Section: Discussion (A) Multiple-criteria Species Delimitationmentioning
confidence: 95%
“…Simulation studies suggest that 5-10 individuals, sequenced at each of 5-10 independent loci provide sufficient power for species delimitation (Zhang et al, 2011), although a larger number of individuals may need to be sampled for genetically diverse taxa. Sampling should also encompass the geographical range of the putative species and incorporate any existing information on diversity.…”
mentioning
confidence: 99%
“…We note that in analyses of both real and simulated data sets the posterior probability of the best fitting model tends to increase quickly with the addition of more loci, with the posterior probability for one model reaching 100% when between 10 and 20 loci are used (Zhang et al 2011). While genome-scale data sets are becoming increasingly common, there appears to be no need to use hundreds of loci for the purpose of species delimitation.…”
Section: Discussionmentioning
confidence: 86%
“…The method is implemented in the Bayesian phylogenetics and phylogeography (BPP) program. In simulation studies BPP was found to perform well, with low false negatives (the error of lumping multiple species into one) and false positives (the error of splitting one species into several), and its performance is virtually unaffected when species experience limited gene flow (e.g., Nm # 0.1) (Zhang et al 2011). Camargo et al (2012 recently compared BPP with several other species-delimitation methods, including a method based on the simulation methodology…”
mentioning
confidence: 99%